Program Management for Strengthening Science and Character Education Learning Outcomes in Vocational Schools throughout Sebatik Nunukan Island - North Kalimantan - Serly Indrawati; Tina Rahmawati (Jurnal Penelitian Pendidikan IPA, 2024)
Research This research examines the management of knowledge strengthening and character education programs in vocational schools throughout Sebatik Nunukan, North Kalimantan. Using a qualitative approach, data was collected through observation, in-depth interviews, and documentation studies with research subjects including teachers, school principals, and students. Data analysis was carried out using thematic methods and the Miles, Huberman, and Saldana model. The research results show that limited educational facilities such as laboratories and libraries hinder the science teaching process. Character education is often inconsistent due to a lack of training and support for teachers, requiring ongoing training and professional support. Local community participation in character education is still limited, even though it is very important to create an environment that supports character values. This research emphasizes the importance of improving educational facilities, continuous training for teachers, community involvement, implementing innovative learning methods, and utilizing technology in programs to strengthen knowledge and character education in vocational schools throughout Sebatik Nunukan. It is hoped that these efforts can improve the quality of education and produce a generation that is competent and has good character.